Effect of solution pH on root architecture of four apple rootstocks grown in an aeroponics nutrient misting system - Farqani, Ali Al; Cheng, Lailiang; Robinson, Terence L.; Fazio, Gennaro (Frontiers in Plant Science, 2024)
The pH level of the soluon in the rhizosphere is an important factor that determines the availability and mobility of nutrients for plant uptake. Soluon pH may also affect root distribuon and architecture of apple rootstocks. In this study, we evaluated the effect of soluon pH on root system development of apple rootstocks using an aeroponics system that was designed and made at Cornell AgriTech Geneva, USA. Four Geneva® apple rootstocks (G.210, G.214, G.41, G.890) were grown in an aeroponic system under nutrient soluon misng featuring connuously adjusted pH levels to three pH treatments (5.5, 6.5 and 8.0). Root development was monitored for 30 days and evaluated regularly for distribuon and root mass. Images of developed roots grown in the aeroponic system were collected at the end of the experiment using a high-resoluon camera and analyzed using GiA Roots® soware which generates root architecture parameter values in a semi-automated fashion. The resulng root architecture analysis showed that Geneva® rootstocks were significantly different by two architecture parameters. The length to width rao analysis represented by two GiA Roots parameters (Minor to Major Ellipse Rao and Network Width to Depth Rao) showed that G.210 was flater when compared to G.890 which had a greater tendency to grow downward. Rootstocks G.214 and G.41 displayed similar growth values. The soluon pH affected most root architecture parameter measurements where overall root growth was higher at pH 8 compared to pH 5.5 and 6.5 which showed similar growth. In general, average root width tended to decrease with higher pH values. While there were no significant differences in leaf nutrient concentraons of P, K, Ca, Mg, S, B, Zn, Cu, and Fe within the four rootstocks, the pH level of the soluon had a significant effect on P, Ca, and Mn. This research is the first of its kind invesgang the effect of pH on root architecture in a soil free (aeroponic) environment and may have implicaons for apple root behavior in field condions where pH levels are different.